2013
DOI: 10.1007/s10551-013-1676-4
|View full text |Cite
|
Sign up to set email alerts
|

Virtue and Vice Attributions in the Business Context: An Experimental Investigation

Abstract: Recent findings in experimental philosophy have revealed that people attribute intentionality, belief, desire, knowledge, and blame asymmetrically to sideeffects depending on whether the agent who produces the side-effect violates or adheres to a norm. Although the original (and still common) test for this effect involved a chairman helping or harming the environment, hardly any of these findings have been applied to business ethics. We review what little exploration of the implications for business ethics has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Inter-rater reliability on coding for 'primary data,' 'secondary data,' 'theoretical paper,' 'cross-sectional,' and 'longitudinal' was all (p \ 0.001) using a binomial distribution. Of 36 highly cited papers on 'virtue' in the Journal of Business Ethics, only eight use primary empirical data (Batson et al 2006;Beadle 2013a, b;Chun 2005;Lau and Wong 2009;Murphy 1999;Robinson et al 2013;Shanahan and Hyman 2003). Most discussions of virtue are conceptual (Alves and Moreira 2013;Arjoon 2000;Chismar 2001;Dierksmeier 2013;Gowri 2007;Hartman 2011;McAdams and Koppensteiner 1992;Melé 2009;Nicholls 2010;Parkan 2008;Sethi 1994;Whetstone 2001).…”
Section: Virtue In Business Ethics: An Aristotelian Account and Focusmentioning
confidence: 99%
See 2 more Smart Citations
“…Inter-rater reliability on coding for 'primary data,' 'secondary data,' 'theoretical paper,' 'cross-sectional,' and 'longitudinal' was all (p \ 0.001) using a binomial distribution. Of 36 highly cited papers on 'virtue' in the Journal of Business Ethics, only eight use primary empirical data (Batson et al 2006;Beadle 2013a, b;Chun 2005;Lau and Wong 2009;Murphy 1999;Robinson et al 2013;Shanahan and Hyman 2003). Most discussions of virtue are conceptual (Alves and Moreira 2013;Arjoon 2000;Chismar 2001;Dierksmeier 2013;Gowri 2007;Hartman 2011;McAdams and Koppensteiner 1992;Melé 2009;Nicholls 2010;Parkan 2008;Sethi 1994;Whetstone 2001).…”
Section: Virtue In Business Ethics: An Aristotelian Account and Focusmentioning
confidence: 99%
“…Bertland 2009;Cavanagh and Bandsuch 2002;Crockett 2005;Hartman and Beck-Dudley 1999;Romar 2002), at times these are quite detailed and context-specific (Drake and Schlachter 2008), but cases are also often explicitly introduced as anecdotal, 'let's consider a true story' (Crockett 2005, p. 199), 'look at what happened to a friend of mine' (Kurzynski 1998, p. 76), or for teaching purposes (Mintz 1996). When data are collected, it is cross section (Batson et al 2006;Beadle 2013a, b;Chun 2005;Lau and Wong 2009;Murphy 1999;Robinson et al 2013;Shanahan and Hyman 2003); an exception-with secondary data-being Cai et al (2011). At the same time, virtue scholars are likely to agree that to apply a virtue lens to a specific setting requires an account of context, tradition, history, and social forces.…”
Section: Virtue In Business Ethics: An Aristotelian Account and Focusmentioning
confidence: 99%
See 1 more Smart Citation
“…For them, it is important to follow the biblical account of creation-that God is a creator and, thus, craftsman, and that it is important to emulate God's character in one's work. Robinsons et al (2013) found that it is the business person's self-interest to be virtuous. In fact, virtue is indeed of value to both business and those concerned with government policy (Flynn 2008) and that virtue is crucial in the Christian ethical heritage.…”
Section: The Virtue Solutionmentioning
confidence: 99%
“…Traditional decision-making approaches often set apart moral and ethical considerations as if these elements would not be of interest in a completely rational choice model (Robinson et al, 2013).…”
Section: Introductionmentioning
confidence: 99%